ABSOLUTE YIELD DETERMINATION OF A 14 - MeV NEUTRON GENERATOR - Baysoy, Derya Yilmaz; Reyhancan, Atilla Iskender; Subasi, Metin (YILDIZ TECHNICAL UNIV, 2011)
In this work absolute neutron yield of a neutron generator was determined using the associated particle method. The experiments were carried out on the SAMES J-15 neutron generator in the fast neutron physics laboratory of the Physics Department at Cekmece Nuclear Research Center. The 14-MeV neutrons were obtained through the H-3(d,n)He-4 reaction by bombarding a solid tritium target with 150 keV deuterons. In the measurements, alpha particles, which are produced simultaneously with the 14-MeV neutrons in the D-T reaction, were counted by a small surface barrier detector placed at 90 degrees with respect to the deuteron beam in the evacuated target chamber. In order to prevent the damage due to fast neutrons and deuterons scattered from the target the detector was covered with a thin Al- foil (0,77) and placed 24 cm away from the target. In evaluating the 14-MeV neutron yield; contribution of D-D neutrons due to the build-up deuterons on the tritium target was taken into account by counting the tritons from the H-2(d,t)He-3 reaction, which occurs simultaneously from the H-3(d,n)He-4 reaction in the target. For comparison, neutron yield was also determined with the neutron activation technique using Al-27(n,p)Mg-27 standard reaction. The results were found to be consistent with each other within the experimental uncertainties.
Keywords: D-T neutron; associated particle method; Sames J-15; Engineering